2014
DOI: 10.18406/2316-1817v7n22015543
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento de cultivares de morangueiro em Maria da Fé e Inconfidentes, sul de Minas Gerais

Abstract: Nos últimos anos a cultura do morango tem-se expandido rapidamente e inúmeras cultivares tem sido introduzidas na região Sul de Minas. A maioria dessas introduções é feita sem avaliações prévias dos materiais nas condições ecológicas das regiões de cultivo, o que muitas vezes, pode levar alguns produtores ao fracasso, visto que a escolha das cultivares é um dos pontos chaves para se obter o sucesso esperado com a cultura. As características das cultivares aliadas às condições ambientais da região e ao manejo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 4 publications
1
3
1
5
Order By: Relevance
“…However, the same cultivar, despite producing more fruits, was inferior to Albion for average mass of fruits. These values were much higher than those found by Pádua et al (2015), which found averages of 10.8 and 14.5 for cultivar Albion and 14.6 and 14.1 for cultivar Aromas.…”
Section: Resultscontrasting
confidence: 71%
“…However, the same cultivar, despite producing more fruits, was inferior to Albion for average mass of fruits. These values were much higher than those found by Pádua et al (2015), which found averages of 10.8 and 14.5 for cultivar Albion and 14.6 and 14.1 for cultivar Aromas.…”
Section: Resultscontrasting
confidence: 71%
“…For the cultivar factor, it was observed that the greatest number of fruits was obtained using the cultivars Festival and Oso Grande, already considered the most commercially productive (Figure 2). These isolated results for the cultivar factor were already expected, since Oso Grande and Festival are cultivars highly adapted to the growing region, presenting a greater number of fruits in commercial plantations, as already reported by other authors (PEREIRA et al, 2013;PÁDUA et al, 2015).…”
Section: Resultssupporting
confidence: 85%
“…One of the most important aspects in planning a commercial cultivation of strawberries is the correct choice of cultivar, which must be adapted to conditions of the growing site (Pádua et al, 2015). The main environmental factors that determine the adaptability of strawberry cultivars are the photoperiod, temperature and the interaction between these factors (Sønsteby & Heide, 2017).…”
Section: Introductionmentioning
confidence: 99%